Field experiments underestimate aboveground biomass response to drought - Kröel-Dulay, György; Mojzes, Andrea; Szitár, Katalin; Bahn, Michael; Batáry, Péter; Beier, Claus; Bilton, Mark; De Boeck, Hans J; Dukes, Jeffrey S; Estiarte, Marc; Holub, Petr; Jentsch, Anke; et al. (Nature ecology & evolution, 2022)
Researchers use both experiments and observations to study the impacts of climate change on ecosystems, but results from these contrasting approaches have not been systematically compared for droughts. Using a meta-analysis and accounting for potential confounding factors, we demonstrate that aboveground biomass responded only about half as much to experimentally imposed drought events as to natural droughts. Our findings indicate that experimental results may underestimate climate change impacts and highlight the need to integrate results across approaches.
Keywords: klimatické změny; období sucha; Biomass; biomasa; Climate Change; Droughts; ekosystém; Ecosystem